Endoscopic observation of different repair patterns in human traumatic tympanic membrane perforations - Huang,Peng (2018)
Abstract Introduction: In the last decade, there has been an increasing use of biomaterial patches in the regeneration of traumatic tympanic membrane perforations. The major advantages of biomaterial patches are to provisionally restore the physiological function of the middle ear, thereby immediately improving ear symptoms, and act as a scaffold for epithelium migration. However, whether there are additional biological effects on eardrum regeneration is unclear for biological material patching in the clinic. Objective: This study evaluated the healing response for different repair patterns in human traumatic tympanic membrane perforations by endoscopic observation. Methods: In total, 114 patients with traumatic tympanic membrane perforations were allocated sequentially to two groups: the spontaneous healing group (n = 57) and Gelfoam patch-treated group (n = 57). The closure rate, closure time, and rate of otorrhea were compared between the groups at 3 months. Results: Ultimately, 107 patients were analyzed in the two groups (52 patients in the spontaneous healing group vs. 55 patients in the Gelfoam patch-treated group). The overall closure rate at the end of the 3 month follow-up period was 90.4% in the spontaneous healing group and 94.5% in the Gelfoam patch-treated group; the difference was not statistically significant (p > 0.05). However, the total average closure time was significantly different between the two groups (26.8 ± 9.1 days in the spontaneous healing group vs. 14.7 ± 9.1 days in the Gelfoam patch-treated group, p < 0.01). In addition, the closure rate was not significantly different between the spontaneous healing group and Gelfoam patch-treated group regardless of the perforation size. The closure time in the Gelfoam patch-treated group was significantly shorter than that in the spontaneous healing group regardless of the perforation size (small perforations: 7.1 ± 1.6 days vs. 12.6 ± 3.9, medium-sized perforations: 13.3 ± 2.2 days vs. 21.8 ± 4.2 days, and large perforations: 21.2 ± 4.7 days vs. 38.4 ± 5.7 days; p < 0.01). Conclusion: In the regeneration of traumatic tympanic membrane perforations, Gelfoam patching not only plays a scaffolding role for epithelial migration, it also promotes edema and hyperplasia of granulation tissue at the edges of the perforation and accelerates eardrum healing.